Pathways, technology and the patient—connected health through the lifecycle - MacMahon, Silvana Togneri; Richardson, Ita (Frontiers in Digital Health, 2023)
Connected Health solutions are ubiquitous in providing patient centered care and in responding to a new paradigm of care pathways where Health Information Technology is being introduced. This paper defines Connected Health, and, in particular, describes standards and regulations which are important to the implementation of safe, effective and secure Connected Health solutions. This paper provides: a holistic view of Connected Health; provides a standards and regulations based view of the lifecycle of the Health IT system; and identifies the relevant roles and responsibilities at the various stages of the lifecycle for both manufacturers of connected health solution and healthcare delivery organization solutions.We discuss how the implementation of standards and regulations, while implementing and using the Health IT infrastructure, requires close collaboration and ongoing communication between Healthcare Delivery Organizations and Accountable Manufacturers throughout the lifecycle of the Health IT system. Furthermore, bringing technology into the healthcare system requires a robust and comprehensive approach to Clinical Change Management to support the business and clinical changes that the implementation of such solutions requires. Ultimately, to implement safe, effective and secure Connected Health solutions in the healthcare ecosystem, it requires that all those involved work together so that the main requirement – patient-centered care – is realized.